1084 CPAP Adherence Varies with Type of Patient Insurance. (27th April 2018) - Mastromatto, N; Killough, N; Keenan, B T; Schwab, R; Staley, B; Simonsen, S; Bergmann, A; Bae, C; Schutte-Rodin, S
Abstract: Introduction: We previously analyzed CPAP use times in our urban sleep clinic before and after the 2009 CMS compliance rules for ongoing PAP coverage >90 days. We found no difference in use times despite changes in insurance rules, workflow and adherence interventions or ongoing mask, unit, tracking technology changes (2011 APSS abstract: CPAP Treatment Adherence in CPAP Clinics: Schutte-Rodin et al). Here, we examine whether type of insurance is associated with CPAP adherence rates. Methods: CPAP compliance rates were evaluated over a 30-month period (January 2015 to June 2017) among patients with Commercial insurance, Medicaid, Medicare or other insurance. Compliance was defined using the standard CMS rule PAP use times. We compared compliance rates among and between insurance carriers using chi-squared tests. Results: De-identified data were analyzed for 4, 285 patients with new PAPs set-up by a DME between January 1, 2015 and June 30, 2017. A total of 1776 (41.4%) of patients had Commercial insurance, 641 (15.0%) Medicaid, 1251 (29.2%) Medicare, and 617 (14.4%) had another or no insurance. The average PAP compliance among all patients was 68.6%. There were significant differences in compliance rates among insurance carriers (p<0.0001), with compliance rates among Commercial (73.9%) and Medicare (73.7%) patients significantly higher than compliance rates among patients with Medicaid (55.1%) or other or no insurance (57.4%). Conclusion: The identification of groups at increased risk of non-adherence to PAP is important in improving overall treatment adherence and efficacy, and, relatedly, in identifying risk-specific interventions to improve patient outcomes. Our data indicate that insurance type is an important predictor of CPAP adherence. Further studies are needed to understand the related factors mediating these associations. Additionally, given the increased focus on quality measures and provider pay for performance, and the expected negative effect of lower adherence, these factors should also be taken into account when evaluating performance metrics of individual providers, hospitals and DMEs. Support (If Any): none.